Fixed Orthodontic Treatment in Cases of Crowding and Loss of the First Molar of the Lower Jaw: A Case Report: Perawatan Ortodonti Cekat Pada Kasus Berdesakan dan Kehilangan Molar Pertama Rahang Bawah : Studi Kasus - Setyawardana, Eka; Sari, Wanda Karisma Dian; Dayanti, Marisa Elvi (Universitas Muhammadiyah Sidoarjo, 2025)
A 15-year-old female patient presented with severe anterior crowding in both the maxillary and mandibular arches. The patient expressed concern regarding facial esthetics and a convex profile and had a history of retained root fragments in the mandibular right and left first molars, as well as persistence of primary teeth in the regions of teeth 55 and 65. A midline deviation was also observed. Clinical examination revealed a Class I molar relationship, while cephalometric analysis showed a skeletal Class II tendency. The upper right and left first premolars were extracted to relieve anterior crowding. The space resulting from the loss of the mandibular first molars was utilized to align the crowded lower teeth. This extraction strategy was employed to improve the vertical dimension and enhance the patient's facial profile. In conclusion, extraction of the maxillary first premolars can be considered as one of the treatment options for managing dental crowding. Extraction-based treatment may help achieve an esthetically pleasing and functionally stable occlusion. Highlights: Severe anterior crowding managed with upper first premolar extractions. Mandibular molar space utilized for alignment and vertical control. Extraction approach improved facial profile and occlusal stability. Keywords: Dental Crowding, Premolar Extraction, Skeletal Class II, Facial Esthetics, Orthodontic Treatment